An experimental study on thermo-catalytic pyrolysis of plastic waste using a continuous pyrolyser. (September 2017) - Auxilio, Anthony R.; Choo, Wei-Lit; Kohli, Isha; Chakravartula Srivatsa, Srikanth; Bhattacharya, Sankar
Highlights: Thermo-catalytic pyrolysis of plastic waste in a bench scale continuous feed unit. Utilizing RDC temperature profile to enhance oil product selectivity towards diesel. Mesoporosity is a critical factor for coke deposition on catalyst. Pelletised catalysts, not powder catalysts, provided higher selectivity towards diesel. Abstract: A bench scale, two-stage, thermo-catalytic reactor equipped with a continuous feeding system was used to pyrolyse pure and waste plastics. Experiments using five zeolitic and clay-based catalysts of different forms (pellet and powders) and different plastic feedstocks – virgin HDPE, HDPE w1aste and mixed plastic waste (MPW) were compared to the control experiments – pyrolysis without catalyst. Results indicated that the two pelletized catalysts were the most promising for the conditions employed. Of these two, one with higher acidity and surface area was highly selective for the gasoline fraction (C5 –C11 ) giving 80% from the total medium distillate conversion using virgin HDPE as feedstock. It also produced the least amount of olefins (17% for virgin HDPE, 4% for HDPE waste and 2% for MPW) and coke (<1% for virgin HDPE, 3% for HDPE waste and 5% for MPW), and the highest aromatics content (22% for virgin HDPE from un-distilled medium distillate, 5% for HDPE and 13% for MPW both from distilled medium distillate). The second pelletized catalyst exhibited high selectivity for the diesel fraction (C12 –C25 ) giving 63% from the total medium distillate conversion using virgin HDPE as feedstock. The amount of coke deposited on the catalyst surface depended mainly on the mesopore volume, with less coke deposited as the mesopore volume increased. The variation in catalyst selectivity with acidity strength due to Lewis sites on the catalyst surface controls selectivity towards carbon chain length.